Gender roles in Ireland : three decades of attitude change - Fine-Davis, Margret (Abingdon, Oxon : Routledge, 2015)
'Gender Roles in Ireland: Three Decades of Attitude Change documents changing attitudes toward the role of women in Ireland from 1975-2005, a key period of social change in this society. The book presents replicated measures from four separate surveys carried out over three decades. These cover a wide range of gender role attitudes as well as key social issues concerning the role of women in Ireland, including equal pay, equal employment opportunity, maternal employment, contraception etc. Attitudes to abortion, divorce and moral issues are also presented and discussed in the context of people's voting behaviour in national referenda. Taken together, the data available in these studies paint a detailed and complex picture of the evolving role of women in Ireland during a period of rapid social change and key developments in social legislation. The book brings the results up to the present by including new data on current gender role issues from Margret Fine-Davis' latest research'--
Includes bibliographical references and index.
Keywords: Sex role -- Ireland -- Public opinion; Women -- Ireland -- Public opinion; Women -- Ireland -- Social conditions; Women -- Ireland -- Economic conditions; Feminism -- Ireland -- Public opinion; Public opinion -- Ireland